Sodium Ion Batteries: Toward High Energy Density All Solid‐State Sodium Batteries with Excellent Flexibility (Adv. Energy Mater. 12/2020). Issue 12 (26th March 2020) - Yao, Yu; Wei, Zhenyao; Wang, Haiyun; Huang, Huijuan; Jiang, Yu; Wu, Xiaojun; Yao, Xiayin; Wu, Zhong‐Shuai; Yu, Yan
Abstract : In article number 1903698, Xiayin Yao, Zhong‐Shuai Wu, Yan Yu and co‐workers design an ultrahigh energy density (1503 Wh kg −1 based on the cathode active material) aqueous Zn–Mn 2+ battery by coupling an acid‐alkaline dual electrolyte and dual dissolution/deposition reactions of both the anode and cathode. The new Zn–Mn 2+ batteries show high coulombic efficiency and excellent cycling stability.